A new approach to the determination of warp-weft densities in textile fabrics by using an image processing technique - (:unkn) unknown (Association Nonwoven Fabrics Industry, 2014)
This paper presents a new approach for processing images of woven fabrics to determine the warp-weft densities. This approach includes three main steps, namely; image transformation, image enhancement, and analyzing signals of the image. In the experimental process, 19 different woven fabric images were scanned at a high resolution (2400 dpi); then these images were transferred to the MATLAB program. By using the vertical and horizontal frequencies of the textile image, the FFT analyses were carried out. Consequently with 97% accuracy, the densities were predicted only by using the images instead of counting them by hand.
Keywords: Image processing; Textile fabrics; Warp weft densities